2019
DOI: 10.1108/jaar-04-2019-0061
|View full text |Cite
|
Sign up to set email alerts
|

The effects of length of service and ethical ideologies on moral development and behavioral intentions

Abstract: Purpose The purpose of this paper is to examine the effects of length of service and ethical ideologies on cognitive moral development (CMD) and ethical behavioral intentions among public sector tax auditors in Brazil. Design/methodology/approach The research data were collected via survey questionnaires from a sample of 625 auditors who work for the Brazilian tax authority. Participants voluntarily complete an online instrument which included three scenarios with context-specific moral dilemmas, questions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Civil servants' high client commitment may result in a value conflict between organizational and client interest when faced with red tape and strict bureaucratic rules, in which compassion overrules intent to comply (Keiser & Soss, 1998; Weißmüller et al, 2022). Conversely, individuals with a lack of moral reasoning are found to be more corrupt (Malagueño et al, 2020; Pelletier & Bligh, 2008) and will easily derive not only motivation but self‐serving rationalization to morally justify their corrupt actions (De Waele et al, 2021). This effect is accelerated by client narratives that serve to morally justify the breach of psychological contracts between the organization and the public agent in favor of prosocial or self‐serving noncompliant behavior to morally justify bureaucratic rule breaking as a workaround for red tape (Meza & Zizumbo‐Colunga, 2021; Shaheen et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Civil servants' high client commitment may result in a value conflict between organizational and client interest when faced with red tape and strict bureaucratic rules, in which compassion overrules intent to comply (Keiser & Soss, 1998; Weißmüller et al, 2022). Conversely, individuals with a lack of moral reasoning are found to be more corrupt (Malagueño et al, 2020; Pelletier & Bligh, 2008) and will easily derive not only motivation but self‐serving rationalization to morally justify their corrupt actions (De Waele et al, 2021). This effect is accelerated by client narratives that serve to morally justify the breach of psychological contracts between the organization and the public agent in favor of prosocial or self‐serving noncompliant behavior to morally justify bureaucratic rule breaking as a workaround for red tape (Meza & Zizumbo‐Colunga, 2021; Shaheen et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Forsyth (1980) argued that the ethics position of individuals is determined by their moral philosophy. In fact, Malagueño et al (2020) found a direct and significant relationship between ethical ideologies and ethical behavioral intentions. Ethics position is established considering two categories: idealism and relativism.…”
Section: Hypothesismentioning
confidence: 93%
“…Civil servants with high levels of PSM (Kwon 2014;Moloney and Chu 2016;Ripoll and Breaugh 2019) and a strong, idealistic code of values are less likely to engage in or tolerate darker shades of corruption (Malagueño et al 2020). The reason is that these individuals associate higher individual moral costs with corrupt behavior, and they exhibit a higher awareness of the harmfulness of corrupt behavior for others and society at large, which prevents their engagement in such acts (Sööt and Rootalu 2012;Ashkanasy, Falkus, and Callan 2000;Ripoll and Breaugh 2019;Davis 2004).…”
Section: Research Question 2: Micro-foundations Of Administrative Cor...mentioning
confidence: 99%
“…Consequently, individuals with a lack of moral reasoning are found to be more corrupt (Pelletier and Bligh 2008;Malagueño et al 2020) and will easily derive not only motivation but self-serving rationalization to morally justify their corrupt actions (De Waele, Weißmüller, and van Witteloostuijn 2021).…”
Section: Research Question 2: Micro-foundations Of Administrative Cor...mentioning
confidence: 99%